Rozwiązane

wykonaj działania


a) -x2 +2x -3x + 4x2=

b) 4,8a - 2a + ( -3,2a) =

c) 5(x - y -1) -3a( a - 5 ) =

d) ( 3a - 9b ): 3 - ( 24a - 8b ) :4 =

e) ( 2x + 3)2 =

f) ( 2x + 5)( 3x - 2 ) =

g) n2(n - 2)(n +3) =

h) -2x2(x - 7)(x + 1) - ( x2 +3x)2 =



Odpowiedź :

Odpowiedź:

a) -x2 +2x -3x + 4x2=-x²+-x+4x²=3x²-x

b) 4,8a - 2a + ( -3,2a) =2,8a+(-3,2a)=-0,4a

c) 5(x - y -1) -3a( a - 5 ) =5x-5y-5-3a²-15a

d) ( 3a - 9b ): 3 - ( 24a - 8b ) :4 =a-3b-24a-8b=23a-11b

e) ( 2x + 3)2 =4x²+9

f) ( 2x + 5)( 3x - 2 ) =6x-4x+15x-10=17x-10

g) n2(n - 2)(n +3) =n²+n²+3n-2n-6=2n²+n-6

Inne Pytanie